Review regarding the use of the company for Operation "Tundra." (1943)
Report outlining Operation Tundra and the experience garnered. Taken from microfilm Records of the German Field Command, Armies, National Archives Series T-315, Reel 1621, 210 Inf. Div., folder 45787/3, first frame 000587. Translated by Major James F. Gebhardt, USA (retired)